GLOBAL TRENDS, RISK FACTORS, AND CHALLENGES IN DRUG-RESISTANT TUBERCULOSIS: A SYSTEMATIC REVIEW OF ANTIMICROBIAL RESISTANCE PATTERNS AND DETERMINANTS - Kafwanka, Ruth Chipampe; Chilyabanyama, Rogers; Chirwa, Richard; Chipimo, Mubanga Lackson (Student’s Journal of Health Research Africa, 2025)
Background Drug-resistant tuberculosis (DR-TB) remains one of the greatest threats to global public health, with multidrug-resistant tuberculosis (MDR-TB) and extensively drug-resistant tuberculosis (XDR-TB) posing significant challenges to TB control efforts. While scientific advancements have led to improved diagnostics and treatment options, the continued spread of resistant TB strains threatens to undo decades of progress. This systematic review synthesizes evidence on the global patterns of antimicrobial resistance (AMR) in TB, identifying key determinants, regional variations, and critical gaps in TB management. Materials and Methods A systematic review of published studies was conducted to examine the prevalence, risk factors, diagnostic and treatment challenges, and policy gaps contributing to AMR in TB. Studies were selected based on their focus on MDR-TB and XDR-TB, with a particular emphasis on regional differences, evolving resistance mechanisms, and healthcare system limitations. Results The review highlights significant regional variability in MDR-TB and XDR-TB prevalence, with the highest burden observed in sub-Saharan Africa, South Asia, and Eastern Europe. Increasing evidence suggests that primary MDR-TB transmission rather than treatment failure is driving resistance in high-burden regions, challenging traditional TB control strategies. Key risk factors include previous TB treatment, HIV co-infection, delayed diagnosis, and poor treatment adherence. Diagnostic challenges persist, with limited access to drug susceptibility testing (DST) and delayed MDR-TB detection contributing to prolonged infectious periods. Treatment barriers include adverse drug reactions, financial constraints, and the rising resistance to second-line drugs, particularly fluoroquinolones. Conclusion The growing burden of DR-TB underscores the urgent need for strengthened global TB control strategies, including expanded molecular diagnostics, enhanced adherence support, pharmacovigilance, and infection control measures. Without decisive action, MDR-TB and XDR-TB will continue to spread, increasing treatment failures and mortality rates. Urgent investment in TB research, new drug development, and healthcare infrastructure is critical to containing the global DR-TB epidemic.